The Nexus Between Total Quality Management, Job Satisfaction and Employee Work Engagement in the Food and Beverage Multinational Company in Nigeria - Oluwafemi, Olaoluwa J.; Okon, Samuel Essien (Organizations and Markets in Emerging Economies, 2018)
Adopting total quality management (TQM) program in an organisation may have consequences not only for organisational outcomes but also for employee work behaviour. Therefore, this study investigates the conceptual and empirical link between TQM practices, job satisfaction, and employee work engagement. Cross-sectional survey design, quota, proportionate and simple random sampling were used to draw 300 participants from the study population, out of which 190 responded and n = 183(61%) usable responses to the questionnaire designed for the purpose from employees of a food and beverage multinational company in Lagos metropolis were obtained. Regression and correlation analyses were used to analyse the study data. Significant positive relationship was found between dimensions of TQM practices (leadership and management support, employee participation, training, reward and recognition, and customer focus), job satisfaction and employee work engagement. After controlling for sex, age and experience, job satisfaction and TQM practices construct jointly and independently predicted employee work engagement. Also, job satisfaction partially mediated the relationship between TQM practices and work engagement. The implications of soft TQM implementation on employee job satisfaction for achieving highly engaged workforce are discussed.